Organ damage and iron overload (Hematology Meeting Reports, 2009)
Iron is a metal element essential for life. It is indispensable for several critical functions (O2 transport and others). The normal iron content of the body is approximately 3 to 4 grams. In humans iron exists in the following forms: a. Hemoglobin in circulating red blood cells - about 2.5 gram; b. Iron containing proteins (myoglobin, cytochromes, and catalase) about - 400 mg; c. Iron bound to transferrin in plasma - about 3-7 mg; d. Storage iron. Storage iron has been precisely calculated by quantitative phlebotomy in healthy, voluntary, subjects and is in the form of ferritin or hemosiderin. Adult men have about 1 gram of storage iron (mainly in liver, spleen, and bone marrow). Adult women have less storage iron, depending upon the extent of menses, pregnancies, deliveries, lactation, and iron intake.1 Total body iron content in normal adults is the result of the balance between iron losses and iron absorbed from the diet. Increased absorption of dietary iron, or iron from multiple transfusions will ultimately result in iron overload.